2018
DOI: 10.1016/j.ymthe.2018.07.019
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticles Based on Poly (β-Amino Ester) and HPV16-Targeting CRISPR/shRNA as Potential Drugs for HPV16-Related Cervical Malignancy

Abstract: Persistent high-risk HPV infection is the main cause of cervical cancer. The HPV oncogene E7 plays an important role in HPV carcinogenesis. Currently, HPV vaccines do not offer an effective treatment for women who already present with cervical disease, and recommended periodical cervical screenings are difficult to perform in countries and areas lacking medical resources. Our aim was to develop nanoparticles (NPs) based on poly (β-amino ester) (PBAE) and HPV16 E7-targeting CRISPR/short hairpin RNA (shRNA) to r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 65 publications
1
20
0
Order By: Relevance
“…We and others have previously shown the effects of CRISPR/Cas in cancer models that use xenografts in immunodeficient mice [ 6 , 18 , 19 ]. This misses an important aspect of responses to treatment, namely the immune response itself.…”
Section: Resultsmentioning
confidence: 99%
“…We and others have previously shown the effects of CRISPR/Cas in cancer models that use xenografts in immunodeficient mice [ 6 , 18 , 19 ]. This misses an important aspect of responses to treatment, namely the immune response itself.…”
Section: Resultsmentioning
confidence: 99%
“…Several pathogenic viruses, including hepatitis B virus, human papilloma virus (HPV), herpes virus, and human immunodeficiency virus type I have shown promising results in action with the CRISPR system and also some of these CRISPR-based treatments have entered into the clinical trials [ 52 – 56 ]. For instance, Zhu et al introduced a safe method to target E7 in HPV-induced cervical cancer cells in vaginal context using poly ß-amino ester-based nanoparticles for delivery of CRISPR modules into xenograft tumor models, resulted in the knockout of E7 and thereby suppression of tumor progression [ 57 ]. Moreover, among all CRISPR-based therapeutic advancements, the utmost consideration has been given to the treatment of cancers.…”
Section: Crispr the Treasure Trove Of Gene-editing Technologiesmentioning
confidence: 99%
“…safer gene therapies for HPV-related diseases (14,15). Previous studies have indicated that systemic delivery of CRISPR/Cas9 targeting HPV oncogenes is effective at eliminating established tumors (16)(17)(18)(19). However, Cas9 may cause many unexpected off-target effects.…”
Section: Discussionmentioning
confidence: 99%
“…These results demonstrated the efficacy of CRISPR-Cas13a in regulating the deregulated phenotypes induced by HPV 16/18. Because the E6 HPV genes share no sequence homology to any human genes, knockdown of this gene will not induce death of healthy cells (16).…”
Section: Discussionmentioning
confidence: 99%